Beyond forceful measures: Tanzania's "war on poaching" needs diversified strategies more than militarised tactics (2017) - Mabele, Mathew Bukhi (Capitalism and economic crime in Africa, 2024)
This Briefing looks at the existing strategies to confront poaching in Tanzania. With militarised strategies becoming dominant, the Briefing argues for diversified tactics to counter ‘poaching’, suggesting that bureaucrats and conservationists must put more efforts into addressing root causes of poaching through strategies that go beyond coercive measures.